Three dreamers : a memoir of family - Carcaterra, Lorenzo (Ballantine Books, 2021)
The author of "Sleepers" presents a memoir that pays tribute to his mother, grandmother, and late wife, celebrating their accomplishments as strong women role models and survivors of history who imparted lessons in courage, kindness, and the power of storytelling.